Human Intestinal Enteroids to Evaluate Human Norovirus GII.4 Inactivation by Aged-Green Tea - Randazzo, Walter; Costantini, Veronica; Morantz, Esther K.; Vinjé, Jan (Frontiers in Microbiology, 2020)
Human noroviruses are the leading cause of epidemic and sporadic acute gastroenteritis worldwide and the most common cause of foodborne illness in the US. Several natural compounds, such as aged-green tea extract (aged-GTE), have been suggested as ingestible antiviral agents against human norovirus based on data using murine norovirus and feline calicivirus as surrogates. However, in vitro data showing their effectiveness against infectious human norovirus are lacking. We tested the activity of aged-GTE to inhibit human norovirus in a human intestinal enteroids (HIEs) model and Tulane virus in LLC-MK2 cell culture. HIE monolayers pretreated with aged-GTE at different temperatures showed complete inhibition of human norovirus GII.4 replication at concentrations as low as 1.0 mg/ml for 37°C, 1.75 mg/ml for 21°C and 2.5 mg/ml for 7°C. In contrast, a moderate decrease in Tulane virus infectivity of 0.85, 0.75 and 0.65 log TCID50/ml was observed for 2.5 mg/ml aged-GTE at 37°C, 21°C and 7°C, respectively. Our findings demonstrate that GTE could be an effective natural compound against human norovirus GII.4 while only minimally effective against Tulane virus.